Improvement of Dolly Women Quality through the Women’s School based Self-Reliance - Khoirunnisa, Ratih; ., Septi Ayu Azizah (Journal of Social and Development Sciences, 2014)
Indonesia has abundant human resources in terms of quantity, including women. Statistic data in 2013 mention that the numbers of Indonesian females are 49.66 percent and males are 50.34 percent from 237.641.326 peoples. However, the quality of human resources is still low viewed by the educational development index that puts the state at rank 69 from 127 countries. One proof of the quality of human resources declining in Indonesia is prostitution that continues grow. One of the prostitution areas is Dolly which located in Surabaya, East Java, Indonesia. This activity could despicable in religion and morality, also affect to the physical and psychological health of women. The important thing that must be obtained to advance insight and ethics’ women is an education. Nowadays, education system that requires students to get good grades makes them depressed and cannot improve their skills. Besides, the school system that unites men and women can reduce competitive spirit within students. Students who begin adolescence and love the other also caused uncontrolled relationship. It because students spend a lot of time to have fun than study and increase their skill. To improve the moral and achievement levels, it is necessary to set up a new system for education. The new education system feasible in Dolly is women’s school. In addition to containing general and moral lessons, the school also provides training facilities on a variety of skills that can help women to compete and earn a living.